Risk factors of developing the hungry bone syndrome after parathyroidectomy for primary hyperparathyroidism - Jakubauskas, Matas; Beiša, Virgilijus; Strupas, Kęstutis (Acta medica Lituanica, 2018)
Background. Around 13% of patients undergoing parathyroidectomy for primary hyperparathyroidism (PHPT) postoperatively develop a condition known as the hungry bone syndrome (HBS). Although the condition is quite prevalent, the research in this field is very limited. The aim of our study was to determine possible risk factors of developing HBS after parathyroidectomy for PHPT. Materials and methods. In this study we enrolled patients who underwent parathyroidectomy for PHPT from January 2005 to December 2016 and performed a retrospective analysis. We used the definition of HBS as hypocalcaemia with normal or elevated PTH values. Patients were divided into two groups by the postoperative HBS prevalence: patients with postoperative HBS and those without postoperative HBS. Results. In all, 94 patients were included into the final analysis. We found that patients who developed HBS more often underwent parathyroidectomies simultaneously with a thyroid surgery, underwent longer operations (73.9 ± 41.7 vs. 102.4 ± 44.8 minutes; p = 0.001), and had heavier parathyroid glands removed (0.6 (0.3–8.0) vs. 0.8 (0.15–14.0) g; p = 0.041). Also, these patients had higher preoperative PTH values (15.3 (6.1–63.7) vs. 22.4 (9.2– 47.8) pmol/l; p = 0.003). From the ROC curve of the preoperative PTH values and the development of the hungry bone syndrome (AUC = 0.721 (95% CI 0.59–0.85); p = 0.003) we found a 45 pmol/l PTH cut-off value that shows a 90% tendency to develop postoperative HBS. Conclusions. Patients undergoing longer parathyroidectomies and those with heavier removed parathyroid glands tend to develop HBS. A preoperative PTH value higher than 45 pmol/l determines an over 90% risk of developing HBS.